How do they measure up? Differences in stakeholder perceptions of quality measures used in English community nursing. Issue 3 (July 2020) - Pollard, Katherine; Horrocks, Sue; Duncan, Lorna; Petsoulas, Christina; Allen, Pauline; Cameron, Ailsa; Cook, Jane; Gibbard, Emma; Harland, Lizanne; Husband, Pete; Loydon, Geoff; McDonald, Ruth; et al.
Objectives: To establish how quality indicators used in English community nursing are selected and applied, and their perceived usefulness to service users, commissioners and service providers. Methods: A qualitative multi-site case study was conducted with five commissioning organizations and their service providers. Participants included commissioners, provider organization managers, nurses and service users. Results: Indicator selection and application often entail complex processes influenced by wider health system and cross-organizational factors. All participants felt that current indicators, while useful for accountability and management purposes, fail to reflect the true quality of community nursing care and may sometimes indirectly compromise care. Conclusions: Valuable resources may be better used for comprehensive system redesign, to ensure that patient, carer and nurse priorities are given equivalence with those of other stakeholders.